Design and evaluation of a virtual private network architecture for collaborating specialist users - Sistani, Akram Kargar Raeespour; Patel, Ahmed Moosajee (Penerbit Universiti Kebangsaan Malaysia, 2016)
The expansion of communication systems is the undeniable advantage of the most contemporary digital technologies. However, when a specialist user such as an inventor or an idea owner communicates through a communication system, their intellects are exposed to theft. Upon the analysis of the requirements of such users, it became evident that in order to implement a global, reliable, yet secure system for specialist users, designing a network architecture that provides centralized private connectivity is crucial. This paper proposes a network architecture that provides centralized private connectivity and accommodates the requirements of the network infrastructure of such a system. The proposed virtual private network (VPN) architecture is designed to provide a trusted environment with centralized control and distributed networking, which is different from existing VPN models. It is entitled as Inventor-Investor Network (IINet) and the name is derived from its significant benefits for inventor and investor sets of users. The real experimental IINet prototype is implemented using OpenVPN. For the purpose of evaluation, round trip time (RTT) is measured and reported as the performance metric based on the different encryption ciphers and digest ciphers as the network metrics.